Internalization in Practice: Early Foreign Direct Investments in Malaysian Tin Mining - Hennart, Jean-francois (Journal of International Business Studies, 1986)
This paper looks at the historical record of early foreign direct investment in Malaysian tin mining and draws its implications for the theory of the MNE.